2010
DOI: 10.3390/molecules15096008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Euphorbia hirta L. Leaf, Flower, Stem and Root Extracts for Their Antibacterial and Antifungal Activity and Brine Shrimp Lethality

Abstract: The antimicrobial activities of the methanolic extracts of Euphorbia hirta Lleaves, flowers, stems and roots were evaluated against some medically important bacteria and yeast using the agar disc diffusion method. Four Gram positive (Staphylococcus aureus, Micrococcus sp., Bacillus subtilis and Bacillus thuringensis), four Gram negative (Escherichia coli, Klebsiella pneumonia, Salmonella typhi and P. mirabilis) and one yeast (Candida albicans) species were screened. Inhibition zones ranged between 16–29 mm. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 10 publications
2
66
2
Order By: Relevance
“…The plant has been reported to contain alkaloids, triterpenoids, phytosterols, tannins, polyphenols and flavonoids [13]. It is among the group of popular herbs used traditionally for the treatment of various diseases such as intestinal parasites, diarrohea, peptic ulcers, heartburn, vomiting, amoebic dysentery, asthma, bronchitis, hay fever, laryngeal spasms, emphysema, coughs, colds, kidney stones, menstrual problems, sterility and veneral diseases [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The plant has been reported to contain alkaloids, triterpenoids, phytosterols, tannins, polyphenols and flavonoids [13]. It is among the group of popular herbs used traditionally for the treatment of various diseases such as intestinal parasites, diarrohea, peptic ulcers, heartburn, vomiting, amoebic dysentery, asthma, bronchitis, hay fever, laryngeal spasms, emphysema, coughs, colds, kidney stones, menstrual problems, sterility and veneral diseases [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by the presence of white milky latex which is more or less toxic [12,13]. It is usually erect, slender-stemmed, and spreading up to 80 cm tall (although sometimes it is seen lying down) [14]. It is an annual broad-leaved herb that has a hairy stem with many branches from the base to the top.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning electron microscopic studies revealed that the cells exposed to leaf extract displayed a rough surface with multiple blends and invaginations which increased with increasing time of treatment. Cells exposed to leaf extract for 36 h showed sever damage, with abundant surface cracks which may be related to final cell collapse and loss of function [76]. The Euphorbia hirta methanol extract showed a potent antimicrobial (MIC 0.250 mg/ml against Escherichia coli and Klebsiella pneumonia [77].The antibacterial activity of the ethanol and petroleum ether extracts of Euphorbia hirta was investigated against Staphylococcus aureus, Salmonella typhi, Pseudomonas aureginosa, Vibrio cholera and Escherichia col.…”
Section: Iii-pharmacological Effectsmentioning
confidence: 99%
“…Five extracts were potential antioxidants: C. dioscoridis, Solanum nigrum, Salvia lanigera, O. syriacum 6 , and Solenostemma arghel 10 . Both C. dioscoridis and E. hirta extracts showed antidiarrheal 11,12 , hypoglycemic 13,14 , and antimicrobial activities 15,16 . In addition, Salvia lanigera aerial parts ether soluble fraction was found to be highly effective against Gram-positive bacteria (Sreptomyces viridochromogenes) 17 .…”
Section: Introductionmentioning
confidence: 99%